AB1068 Disease Burden of Refractory Gouty Arthritis: A One Year Multinational Prospective Observational Study. (10th June 2014) - Bessette, L.; Lioté, F.; Moragues, C.; Moericke, R.; Zhang, Z.; Lecomte, P.; Ferreira, A.; Kessabi, S.; Tian, H.; Li, L.; Singh, J.
Abstract : Background: Refractory gouty arthritis is the most prevalent inflammatory arthritis. It is characterized by frequent attacks and occurs when standard of care for gout is either ineffective, or contraindicated or associated with intolerance or non-compliance. However, there is limited evidence on the burden associated with refractory gout. Objectives: To assess the patient burden and healthcare resource utilization of refractory gout during the presence or absence of flares, over one year. Methods: MOTION was a one year, multinational (6 countries), non-interventional, prospective, observational study in patients with refractory gout, who experienced at least 3 gout attacks in the previous year. Refractory gout was defined as (1) prior or current usage of uric acid-lowering therapy and still experiencing breakthrough flares; (2) refractory to first-line anti-inflammatory therapy (NSAIDs, colchicine, or steroids). Patients were followed up each month, for one year. Primary outcome was assessment of health utility during a refractory gout attack, using the EuroQol Health Status Questionnaire 5D (EQ-5D) index. Secondary outcomes included EQ-5D descriptive system, visual analogue scale (VAS), disease-specific quality of life (QoL) using Gout Assessment Questionnaire–Gout Impact Scale (GAQ-GIS) and healthcare resource utilization. Summary statistics pooled for all visits are presented for patients experiencing and not experiencing flares at the time of the visit (mean for continuous variable and proportions for categorical variables). Results: A total of 454 patients (mean age: 56 years), consisting of 86% males, were included in the analysis. Pooled across all visits, patients having gout flares at the visit had a mean EQ-5D utility level of 0.614 (SD=0.246) compared to 0.867 (SD=0.165) for patients not having a gout flare at the visit. Patients had worse scores on all 5 EQ-5D dimensions when experiencing gout flares. Patients having gout flares had lower mean EQ-5D VAS compared to those without flares: 60.7 (SD=23.75) vs . 79.5 (SD=17.58). The mean scores for five domains of GAQ-GIS that included overall gout concern (81.27 vs . 70.06), medication side effects (59.12 vs . 51.26), unmet need (48.26 vs . 37.19), well-being during attack (57.32 vs . 45.23) and gout concern during attack (63.58 vs . 54.09) were worse in patients with flares than in patients without flares. Moreover, Patients with flares had higher resource utilization compared to those without flares: emergency room visits (21.3% vs . 6.7%), hospitalization rate (15.0% vs . 5.9%), and frequency of doctor visits (62.0% vs . 49.6). Conclusions: Refractory gout leads to increased patient burden and health care resource utilization with diminished QoL suggesting unmet medical needs in this patient population. Disclosure of Interest: L. Bessette Grant/research support: Novartis, F. Lioté Shareholder of: Novartis, Ipsen, Sanofi, Grant/research support: unrestricted grants for the European Crystal Workshop and the first International conference on hyperuricemia and gout from Novartis, SOBI, Astra-Zeneca, Savient, Ipsen, Menarini, Mayoly-Spindler, Consultant for: Novartis, Ipsen, Menarini, Savient, Astra-Seneca, Mayoly-Spindler, C. Moragues Grant/research support: Novartis, R. Moericke Grant/research support: Novartis, Z. Zhang Grant/research support: Novartis, P. Lecomte Employee of: Novartis Pharmaceutical AG, A. Ferreira Employee of: Novartis Pharmaceutical AG, S. Kessabi Employee of: Novartis, H. Tian Employee of: Novartis Pharmaceuticals Corporation, L. Li Employee of: Novartis Pharmaceuticals Corporation, J. Singh Grant/research support: Takeda, Savient, Novartis, Consultant for: Savient, Takeda, Regeneron and Allergan DOI: 10.1136/annrheumdis-2014-eular.4215